Mandatory food fortification in the eastern Mediterranean region results in reduced prevalence of neural tube defects - Roozen, Sylvia; Johnson, Quentin; Ibrahim, Eman; Al Maamari, Salima; Barkat, Amina; Al Shammakhi, Saleh; Laamiri, Fatima Zohra; Hassan, Aguenaou; Gamih, Hasnae; Yahyane, Abdelhakim; Al Jawaldeh, Ayoub (Frontiers in Public Health, 2026)
IntroductionNeural Tube Defects (NTDs) are preventable congenital malformations affecting the brain and spinal cord that occur very early in pregnancy, often before gestation is recognized. Globally, at least 20 per 10,000 live births are estimated to be affected by NTDs, although the true prevalence is likely higher due to unreported miscarriages, elective terminations, and gaps in surveillance systems. Mandatory fortification of staple foods with folic acid (Vitamin B9) is widely recognized as the most effective and cost-efficient strategy to reduce the prevalence of NTDs, whereas voluntary dietary supplementation programs have demonstrated limited uptake and population-level impact.MethodsThis study employs a situational analysis of mandatory food fortification policies and programs in the Eastern Mediterranean Region. Available epidemiological data on NTD prevalence were reviewed alongside evidence on folic acid fortification effectiveness and program implementation. The analysis also considered the role of surveillance systems, program coverage, and multisectoral engagement across public, private, and civic sectors to assess feasibility, sustainability, and health impact.ResultsEstimates of the impact of mandatory food fortification programs in the Eastern Mediterranean Region are constrained by heterogeneous data sources, weak or incomplete surveillance systems, and variable program coverage between and within countries. While countries with established fortification policies show potential reductions in NTD prevalence, inconsistent implementation and monitoring limit the ability to accurately measure outcomes. Insufficient coordination among stakeholders further affects program effectiveness and long-term sustainability.DiscussionDespite strong evidence supporting mandatory folic acid fortification as an effective NTD prevention strategy, significant implementation and monitoring challenges persist in the Eastern Mediterranean Region. Strengthening surveillance systems, improving data quality, and enhancing multisectoral collaboration are critical to translating policy commitments into measurable health outcomes. By integrating epidemiological evidence with implementation insights, this analysis identifies priority areas for improving regional fortification efforts and contributes to broader global strategies aimed at reducing the burden of NTDs.